Impaired Duration Perception in Patients With Unilateral Vestibulopathy During Whole-Body Rotation - Kwon, Eunjin; Lee, Ju-Young; Song, Jung-Mi; Kim, Hyo-Jung; Lee, Jong-Hee; Choi, Jeong-Yoon; Kim, Ji-Soo (Frontiers in Integrative Neuroscience, 2022)
This study aimed to evaluate vestibular perception in patients with unilateral vestibulopathy. We recruited 14 patients (9 women, mean age = 59.3 ± 14.3) with unilateral vestibulopathy during the subacute or chronic stage (disease duration = 6 days to 25 years). For the evaluation of position perception, the patients had to estimate the position after whole-body rotation in the yaw plane. The velocity/acceleration perception was evaluated by acquiring decisions of patients regarding which direction would be the faster rotation after a pair of ipsi- and contra-lesional rotations at various velocity/acceleration settings. The duration perception was assessed by collecting decisions of patients for longer rotation directions at each pair of ipsi- and contra-lesional rotations with various velocities and amplitudes. Patients with unilateral vestibulopathy showed position estimates and velocity/acceleration discriminations comparable to healthy controls. However, in duration discrimination, patients had a contralesional bias such that they had a longer perception period for the healthy side during the equal duration and same amplitude rotations. For the complex duration task, where a longer duration was assigned to a smaller rotation amplitude, the precision was significantly lower in the patient group than in the control group. These results indicate persistent impairments of duration perception in unilateral vestibulopathy and favor the intrinsic and distributed timing mechanism of the vestibular system. Complex perceptual tasks may be helpful to disclose hidden perceptual disturbances in unilateral vestibular hypofunction.